2019
DOI: 10.1016/j.envint.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Using deep learning to examine street view green and blue spaces and their associations with geriatric depression in Beijing, China

Abstract: Background Residential green and blue spaces may be therapeutic for the mental health. However, solid evidence on the linkage between exposure to green and blue spaces and mental health among the elderly in non-Western countries is scarce and limited to exposure metrics based on remote sensing images (i.e., land cover and vegetation indices). Such overhead-view measures may fail to capture how people perceive the environment on the site. Objective This study aimed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
241
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 425 publications
(263 citation statements)
references
References 76 publications
(147 reference statements)
15
241
4
3
Order By: Relevance
“…To extract streetscape greenery objects (e.g., plants and trees), a supervised machine learning approach based on semantic image segmentation techniques was implemented [31]. More precisely, we used a fully convolutional neural network for semantic image segmentation (FCN-8s) [38] together with the online ADE20K dataset of annotated images for training purposes [45].…”
Section: Greenery Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To extract streetscape greenery objects (e.g., plants and trees), a supervised machine learning approach based on semantic image segmentation techniques was implemented [31]. More precisely, we used a fully convolutional neural network for semantic image segmentation (FCN-8s) [38] together with the online ADE20K dataset of annotated images for training purposes [45].…”
Section: Greenery Datamentioning
confidence: 99%
“…A preliminary study carried out in Beijing, China, showed that streetscape greenery derived from street view data was inversely 1 As a multi-dimensional construct, mental wellbeing constitutes positive states of psychological, life satisfaction, as well as emotional health [63]. correlated with depressive symptoms among elderly people, while this was not the case for NDVI [31]. This suggests that streetscape greenery is particularly vital in dense Chinese inner cities, where larger areas of greenery are often absent.…”
Section: Introductionmentioning
confidence: 99%
“…of depression is therefore a key public health concern especially for older people (Helbich et al, 2019;Niles & O'Donovan, 2019;Wang, Liu, et al, 2019b;Wang, Lu, et al, 2019c). Compared to young people, older people spend more time in their neighbourhoods due to retirement and functional restriction Wang, Feng, Xue, Liu, & Wu, 2019a;Wiles et al, 2009;Wiles, Leibing, Guberman, Reeve, & Allen, 2012) and neighbourhood environment may play an important role in their daily life.…”
mentioning
confidence: 99%
“…Current studies have utilized different big geodata to assess street networks from different perspectives [16][17][18]. For instance, Long and Liu [19] evaluated street greenery by proposing an automatic method to detect greenery from street view images.…”
Section: Introductionmentioning
confidence: 99%